2020
DOI: 10.1039/d0sc00505c
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced carbocation-enhanced charge transport in single-molecule junctions

Abstract: We report the first example of photo-induced carbocation-enhanced charge transport in triphenylmethane junctions using the scanning tunneling microscopy break junction (STM-BJ) technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Their approach could be used for probing the reaction kinetics, reversibility, and the occurrence of isomerization during the chemical reaction in MJs. In another recent study, using the STM-BJ technique, Bei et al demonstrated photo-induced carbocation-enhanced charge transport in an MJ composed of malachite green leuco hydroxide (MGOH) [65]. As shown in Figure 2c, in the presence of 302 nm UV light, the MGOH produces malachite green carbocations, thus inducing a minor structural change where the orbital hybridization of the central carbon atom changes from initial sp 3 to sp 2 .…”
Section: Photo-induced Conductance Mechanisms In Single Mjsmentioning
confidence: 98%
“…Their approach could be used for probing the reaction kinetics, reversibility, and the occurrence of isomerization during the chemical reaction in MJs. In another recent study, using the STM-BJ technique, Bei et al demonstrated photo-induced carbocation-enhanced charge transport in an MJ composed of malachite green leuco hydroxide (MGOH) [65]. As shown in Figure 2c, in the presence of 302 nm UV light, the MGOH produces malachite green carbocations, thus inducing a minor structural change where the orbital hybridization of the central carbon atom changes from initial sp 3 to sp 2 .…”
Section: Photo-induced Conductance Mechanisms In Single Mjsmentioning
confidence: 98%
“…For instance, the photo‐driven reaction of malachite green leucoethanol (MGOH) molecules, which are precursors of carbocations, has been studied at the single‐molecule level by using the STM‐BJ technique ( Figure a). [ 100 ] Specifically, in the presence of 302 nm UV light, MGOH efficiently produces malachite green carbocations (MG + ) and hydroxide ions. To confirm the formation of the carbocations, the UV–vis absorption spectra of MGOH before and after UV irradiation are tested.…”
Section: Photoinduced Reactionsmentioning
confidence: 99%
“…b)Schematic representation of the energy level structures for charge transport before and after the formation of a carbocation. Reproduced with permission [100]. Copyright 2019, The Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…With this in mind, in this work, we presented the first experimental demonstration of monitoring excited-state bent-to-planar motions at the single-molecule scale by photoconductance. The DPAC derivative with SMe anchoring groups ( DPAC-SMe , Figure b) was designed as a molecular prototype, which was utilized to fabricate single-molecule junctions using the scanning tunneling microscope break junction technique (STM-BJ). By imposing continuous 340 nm light irradiation, the single-molecule junctions of DPAC-SMe exhibited a distinguished and reversible photoconductance of up to ∼200% than that without irradiation, making it one of the largest photoconductance values with high stability among the reported single-molecule junctions, benefiting from the unique bent-to-planar photocycle between the ground and excited states. This differed significantly from the traditional photoswitching behavior in single-molecule junctions, referring to the steady structural and correspondingly drastic ground-state changes after irradiation, along with resulting irreversible conductances in the absence of other stimuli, such as different wavelengths of light or heat. The DPAC-SMe -fabricated junctions also exhibited in situ conductance modulation as pulsed 340 nm light irradiation.…”
Section: Introductionmentioning
confidence: 99%